Cloud migration vs. cloud native : considerations for migrating to the cloud - Garrison, Justin (O'Reilly Media, 2018)
You've seen your organization's future and it clearly includes cloud computing. Question is, how do you get there? Do you migrate your existing infrastructure and services, or rebuild your technology and go cloud native? This article examines the pros and cons of each approach, and looks into non-technical considerations involving people, processes, and costs.